The Effect of Using Integrated Education on Cognitive Achievement and Survival of the Effect of Learning for First Year Secondary School Students in Chemistry(1)Experimental Research on High School Students Safia Bint Abdulmutallab, Jeddah, Saudi Arabia - AbuZaherah, Nadia Obidullah (Journal of Educational and Psychological Sciences, 2020)
The study aimed to know the impact of using integrated education on cognitive achievement and the survival effect of learning for first year secondary school students in chemistry (1).To achieve this goal, the researcher used the experimental method, where 3 experimental samples and 4 control officers were selected. In the post-test as well as in the postponed test for the benefit of the experimental sample and in the light of these results the researcher recommended the need to adopt integrated education in public education and the education of older women and special needs and provide the appropriate environment for its application
Keywords: Blended Learning; Learning Impact; Cognitive Achievement; Chemistry (1)